DEVELOPMENT OF VALUE ADDED PRODUCTS (BUN, MUFFIN, NOODLES AND NUGGETS) BY SUBSTITUTION WITH CARISSA SPINARUM AND FICUS CARICA POWDER - Chauhan, Ambika (Asian Journal of Pharmaceutical and Clinical Research, 2016)
In the present investigation attempts have been made to develop nutrient rich value added products (bun, muffin, noodles and nuggets) by the substitution of Carissa spinarum and Ficus carica powder in the proportion (100:0, 100:15, 100:30, 100:45).The nutritional composition, dietary fibre composition and mineral composition of ( bun, muffin, noodles and nuggets) and organoleptic evaluation for bun and muffin (made with fresh whole fruits )were investigated by standard selected methods. Result revealed that after the substitution of selected fruits in formulated value added products the nutritional composition (moisture, ash, carbohydrates, protein and fat content),dietary fiber ( NDF, ADF, hemicellulose, cellulose and lignin content ) and mineral composition (calcium, iron and phosphorus) will increased. The organoleptic test showed that the substitution of 15 per cent fresh Carissa spinarum and 30 per cent of Ficus carica were more acceptable in case of bun and muffins.